Ornamented Worlds and Textures of Feeling: The Power of Abundance - Jaan Valsiner (Outlines, 2008)
Human development takes place in an ornamented – redundantly patterned and highly repetitive – world. The emergence of knowledge takes the form of episodic unpredictable synthetic events at the intersection of the fields of internal and external cultural meaning systems – through the mutually linked processes of constructive internalization and externalization. Patterns of decorations – ornaments – are relevant as redundant “inputs” into the internalization/externalization processes. Ornaments can be viewed not merely as "aesthetic accessories" to human activity contexts but as holistic devices of cultural guidance of human conduct that acts through the subjectivity of personal feelings. This guidance is peripheral in its nature – surrounding the ordinary life activities with affectively oriented textures of cultural meanings.